Examine the Mechanical Properties of Aluminium Tetrahydride/Calotropis gigantea Based Hybrid Polyester Composites in Cryogenic Atmosphere - Pavan Balappa Bagali; N. I. Haroon Rashid; Essam A. Al-Ammar; C. Srinivas; H. V. Jayaprakash; J. D. Venkatesh; Sohail M. A. K. Mohammed; Melvin Victor De Poures; Nahom Adugna (Advances in Polymer Technology)
From the previous scarce periods, the investigation has evolved from traditional resources and compounds and toward frivolous constituents to produce small and hugely influential substances for specific purposes. The foremost goal of the current examination is to explore the effectiveness of aluminium tetrahydride (ATH) filler addition on the Calotropis gigantea fibre (CGF)/polyester-based hybrid composite. The hybrid materials with a 3 mm width and three layers of CGF were manufactured using the conventional technique. To achieve the objectives mentioned above, the following constraints like (i) Wt.% of ATH, (ii) number of CGF Layers, and (iii) cryogenic treatment hours, each at three different levels, were chosen. The composite was fabricated as per the design of L9 orthogonal array. This research measured the mechanical characteristics like flexural, tensile, and impact characteristics. The materials with 5 wt proportions of filler, 3 layers of CGF and 30 min of liquid nitrogen treatment (A2, B3 and C2) showed better mechanical strength. They were studying the broken specimen's morphological behavior by scanning electron microscopy (SEM).